Institutional Efficiency And Financial Performance Of Insurance Companies In Nigeria - Ogunwale, Olurotimi; Akintoye, Ishola Rufus; Ogboi, Charles; Ogbebor, Peter Ifeanyi (Archives of Business Research, 2024)
This study investigated the impact of institutional efficiency on the financial performance of insurance companies in Nigeria covering the period from 2011 to 2022. The study employed an ex-post facto research design, the estimation techniques utilized were feasible generalized least squares (FGLS) on a sample of five insurance companies were taken. The key variables used in the analysis included net profit margin (NPM) as dependent variable and claims processing efficiency (CPE), risk management effectiveness (RME), and regulatory compliance (RC) as independent variables. The findings displayed that claims processing efficiency (β =0.185, p > 0.05) had positive but no significant effect with net profit margin, risk management effectiveness rate (β =105.910, p > 0.05) is positive but not significantly influencing in net profit margin, regulatory compliance also have negative but does not significantly impact net profit margin of the selected insurance companies in Nigeria at 1% level (β =-12.504, p > 0.05). The study thus recommended, among others, that policy maker should encourage insurance companies to adopt measures that enhance institutional efficiency, such as investing in technology, improving risk management practices, and enhancing customer service.